PEMAMFAATAN LIMBAH KULIT BUAH AREN SEBAGAI PUPUK KOMPOS TERHADAP EVALUASI NUTRISI SILASE RUMPUT GAJAH PADA TERNAK RUMINANSIA - Angelia Utari (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2018)
The giving of food can affect the quality of forage production in cattle ruminasia. Forage feed improvement through a process of fermentation on elephant grass generally improves the quality of fodder production generates high basalt, the value of nutrition, and the quality of the meat on the ruminant livestock. Utilization of compost waste that comes from the skin of the fruit of the areca palm (Arenga pinnata) is a versatile plant. It is used in the food industry produces waste fruit skins that can be used as a biomass plant. The existence of the HMT (Forage Forage) as fresh forage preservation called silage is expected to be one of the solutions to overcome the problem of shortage of fresh forage during the difficulties of feeding, besides making silage intended to maintain the quality or even the enhance the quality of the HMT. Fermentation feed full/complete feed (CF)-based forage feed as fodder of ruminants can be applied, either in the household or industrial scale. Full feed technology may be the solution over the question of the quality of the feed and the feed stock. Nutritional value can be set by specifying the number and type of livestock do not mix, the opportunity to choose a feed so that minimize waste feed is not edible, practical, and can be stored for a long time. Application of forage forage feeding in the form of silage grass elephants with enclosure systems maintenance generally produced meat with the juice of impression better than field. Keywords:Arenga pinnata, Ruminansia, nutrition